How sleepy patients differ from non‐sleepy patients in mild obstructive sleep apnea?. (29th July 2021) - Oksenberg, Arie; Goizman, Vlada; Eitan, Edith; Nasser, Kitham; Gadoth, Natan; Leppänen, Timo
Summary: To aim is investigate whether demographic, polysomnographic or sleep behaviour data differ between non‐sleepy, sleepy and very sleepy patients with mild obstructive sleep apnea. The study population consisted of 439 consecutive adult patients diagnosed with mild obstructive sleep apnea (5 ≤ apnea–hypopnea index < 15) after a complete polysomnographic evaluation. The patients were divided into three groups based on subjective sleepiness: very sleepy (Epworth Sleepiness Scale ≥ 16, n  = 59); sleepy (10 < Epworth Sleepiness Scale < 16, n  = 102); and non‐sleepy (Epworth Sleepiness Scale ≤ 10, n  = 278). Demographic, polysomnographic and sleep behaviour data were compared between the groups. There were no statistically significant differences in breathing abnormality indices and most of the demographic features between the groups. The number of arousals was significantly higher in the very sleepy group compared with the non‐sleepy group (140.8 ± 105.2 versus 107.6 ± 72.2). Very sleepy patients reported feeling sleepy during the daytime more often (42.4% versus 31.7%) and sleeping significantly less during the week compared with non‐sleepy patients. Also, a significantly higher proportion of sleepy (47.1%) and very sleepy patients (44.1%) reported taking naps during weekends compared with non‐sleepy patients (35.6%). In a regression analysis, also total sleep time ( β  = 0.045), sleep efficiency ( β  = −0.160), apnea index ( β  = −0.397), apnea–hypopnea index in supine position ( β  = 0.044), periodic limb movement index ( β  = 0.196) and periodic limb movement‐related arousal index ( β  = −0.210) affected subjective daytime sleepiness. The results suggest that excessive daytime sleepiness in patients with mild obstructive sleep apnea appears to be related to inadequate sleeping habits (i.e. insufficient sleep during working days) and decreased sleep quality rather than differences in breathing abnormalities.